(untitled) (Journal of history-rus, 2025)
The aim of this study is to conduct a comprehensive analysis of the causes, preconditions, and mechanisms underlying the formation of urban culture in medieval Kazakhstan, with a particular focus on the socio-economic, political, and cultural role of cities within the framework of the Kazakh Khanate. In the context of a predominantly nomadic economy, the emergence of stable urban centers in southern Kazakhstan represents a complex historical and civilizational phenomenon that requires a multifaceted analytical approach. The study addresses several key objectives: identifying the geographical and climatic factors that contributed to urbanization in the southern regions; examining the role of the Silk Road as a conduit for economic and cultural exchange; analyzing the impact of the Islamic Renaissance on the architectural, educational, and spiritual development of cities; and exploring the interaction between secular and religious authority in urban environments. The methodology combines historical-sociological, cultural, and comparative-historical approaches. The use of archaeological data, written sources, and historical geography materials enables a long-term perspective on urbanization processes and helps uncover patterns in the interaction between sedentary and nomadic elements. The novelty of the research lies in identifying a distinctly Kazakh model of urbanization as a hybrid system that emerged at the intersection of nomadic and sedentary worlds. For the first time, the strategic role of cities as nodal points between East and West is emphasized, highlighting their function in facilitating trade and transmitting cultural, religious, and political ideas. The study demonstrates that cities served as centers of economic growth and legitimization of the Kazakh Khanate’s authority in the international arena. A key finding is that urbanization in the steppe was not an anomaly but rather a reflection of local communities’ adaptive capacity to global transformations. Cities in Kazakhstan became arenas of cultural synthesis, where Islam, Turkic traditions, local governance, and geopolitical interests converged, positioning medieval Kazakh urban culture as an integral part of the broader Eurasian civilizational landscape.